Disability level’s impact on blood pressure-mortality association in older long-term care adults: evidence from a large Chinese cohort study - Zhong, Yue; Feng, Chuanteng; Hou, Lisha; Yang, Ming; Zhang, Xinjun; Wu, Jinhui; Dong, Birong; Jia, Peng; Yang, Shujuan; Dou, Qingyu (BMC geriatrics, 2024)
Evidence of the optimal blood pressure (BP) target for older adults with disability in long-term care is limited. We aim to analyze the associations of BP with mortality in older adults in long-term care setting with different levels of disability. This prospective cohort study was based on the government-led long-term care programme in Chengdu, China, including 41,004 consecutive disabled adults aged ≥ 60 years. BP was measured during the baseline survey by trained medical personnel using electronic sphygmomanometers. Disability profile was assessed using the Barthel index. The association between blood pressure and mortality was analyzed with doubly robust estimation, which combined exposure model by inverse probability weighting and outcome model fitted with Cox regression. The non-linearity was examined by restricted cubic spline. The primary endpoint was all-cause mortality, and the secondary endpoints were cardiovascular and non-cardiovascular mortality. The associations between systolic blood pressure (SBP) and all-cause mortality were close to a U-shaped curve in mild-moderate disability group (Barthel index ≥ 40), and a reversed J-shaped in severe disability group (Barthel index < 40). In mild-moderate disability group, SBP < 135 mmHg was associated with elevated all-cause mortality risks (HR 1.21, 95% CI, 1.10-1.33), compared to SBP between 135 and 150 mmHg. In severe disability group, SBP < 150 mmHg increased all-cause mortality risks (HR 1.21, 95% CI, 1.16-1.27), compared to SBP between 150 and 170 mmHg. The associations were robust in subgroup analyses in terms of age, gender, cardiovascular comorbidity and antihypertensive treatment. Diastolic blood pressure (DBP) < 67 mmHg (HR 1.29, 95% CI, 1.18-1.42) in mild-moderate disability group and < 79 mmHg (HR 1.15, 95% CI, 1.11-1.20) in severe disability group both demonstrated an increased all-cause mortality risk. The optimal SBP range was found to be higher in older individuals in long-term care with severe disability (150-170mmHg) compared to those with mild to moderate disability (135-150mmHg). This study provides new evidence that antihypertensive treatment should be administered cautiously in severe disability group in long-term care setting. Additionally, assessment of disability using the Barthel index can serve as a valuable tool in customizing the optimal BP management strategy. Chinese Clinical Trial Registry (Registration Number: ChiCTR2100049973).